The challenge of effective speaking - Verderber, Rudolph F.; Verderber, Kathleen S. (Thomson/Wadsworth, 2003)
Wadsworth's best selling Public Speaking text, the Verderbers' CHALLENGE OF EFFECTIVE SPEAKING, features a skills-oriented, mainstream approach that has effectively led hundreds of thousands of students through the challenges they face as they develop and deliver speeches. The speech making process is presented in a six-step framework based on classical and contemporary theory. The straightforward writing style and effective use of examples enables students to understand and effectively perform key speech making activities. The six-step framework emphasizes topic selection, audience analysis and adaptation, effective research (including appropriate use of Internet resources), organization (with emphasis on outlining), language and delivery. The six action steps are introduced in generic form and then later adapted to follow principles of informative and persuasive speaking